(untitled) (Boletin Médico de Postgrado, 2020)
Inflammatory bowel disease (IBD) negatively affects the quality of life of the patient with limitations in their daily activities. A prospective transversal study was performed in 56 patients through the application of the IBDQ – 32 questionnaire in order to evaluate quality of life of patients with inflammatory bowel disease of the Servicio de Gastroenterología, Department of Medicine, Hospital Central Universitario Dr. Antonio María Pineda of Barquisimeto, Lara state. The results show that in treated, controlled, patients, 1 out of 4 have abdominal pain and diarrhea, more than half have rectal evacuatory dysfunction, 1 out of 3 have dyspeptic symptoms and 1 out of 6 complain of abdominal distension. More than half have rectorrhagia of variable intensity. 25% of patients sometimes feel frustration, impatience and restlessness, 26,8% feel discouragement towards the disease and 23,2% show moodiness; 17,9% of patients show symptoms suggestive of depression. IBD is a group of diseases that generate limitation and disability diminishing the quality of life of patients.